Application of a hybrid Entropy–McKinsey Matrix method in evaluating sustainable urbanization: A China case study. (February 2015) - Shen, Liyin; Zhou, Jingyang; Skitmore, Martin; Xia, Bo
Highlights: Discuss the effectiveness of Entropy and GE Matrix method in evaluating the performance of urbanization. Introduce a hybrid Entropy–GE Matrix method for evaluating sustainable urbanization. Give a case study to verify the effectiveness of this hybrid Entropy–GE Matrix method. Abstract: Although urbanization can promote social and economic development, it can also cause various problems. As the key decision makers of urbanization, local governments should be able to evaluate urbanization performance, summarize experiences, and find problems caused by urbanization. This paper introduces a hybrid Entropy–McKinsey Matrix method for evaluating sustainable urbanization. The McKinsey Matrix is commonly referred to as the GE Matrix. The values of a development index (DI) and coordination index (CI) are calculated by employing the Entropy method and are used as a basis for constructing a GE Matrix. The matrix can assist in assessing sustainable urbanization performance by locating the urbanization state point. A case study of the city of Jinan in China demonstrates the process of using the evaluation method. The case study reveals that the method is an effective tool in helping policy makers understand the performance of urban sustainability and therefore formulate suitable strategies for guiding urbanization toward better sustainability.